Evaluation of changes in plasma levels of MMP-8, MMP-13, and Thrombospondin 2 in patients with Osgood–Schlatter disease (OSD) - Kulesza, Monika; Guszczyn, Tomasz; Kicman, Aleksandra; Marecki, Rafał; Kicman, Michał Stanisław; Ławicki, Sławomir (Frontiers in Molecular Biosciences, 2025)
IntroductionOsgood-Schlatter disease (OSD) is characterized by its relatively frequent occurrence and unknown pathomechanism. It mainly affects young athletes. Matrix metalloproteinases (MMPs) may be involved in the pathogenesis, while Thrombospondin 2 is involved in healing process. Purpose of this study was to determine changes in MMP-8, MMP-13 and Thrombospondin 2 levels in patients with OSD compared to control group (CG).MethodsThe study was conducted on 140 patients with OSD (age range: 11–15), CG consisted of 100 individuals with minor hand injuries (age range: 12–15). Levels of MMPs and Thrombospondin 2 were determined in plasma using an immunoenzymatic method (ELISA).ResultsConcentrations of MMP-13 (median: 496.5 ng/mL; p < 0.0001) and Thrombospondin 2 (median: 21.05 pg/mL; p < 0.0001) were higher in patients with OSD, while MMP-8 values (median: 26.60 ng/mL; p < 0.001) were lower in patients with OSD compared to CG (58.08 ng/mL; 14.43 pg/mL; 95.91 ng/mL; respectively). Significant correlations were found between the parameters studied, and the highest AUC (area under curve) was obtained for MMP-13 in the OSD group.DiscussionThe studied compounds have potential as additional tests to distinguish OSD from other diseases, and MMP-13 may be involved in the pathogenesis of OSD.